(untitled) (Forum Theologicum Sardicense, 2025)
Rusinna Torosyan, God-Man Intimacy, Communication and Love, according to the Theology of Fr. Georges Florovsky. This article aims to highlight some of the testimonies found in the theology of Fr. G. Florovski regarding the God-man intimacy and communication. Also it wants to emphasize the importance God-man closeness has for the wellbeing of man and for theology in general. An eschatological analysis of modernity is made, pointing out the negative consequences from the human distancing from God. The call for creativity and creative life is at the heart of the father‘s message, as a way to acquire the Spirit and return to spirituality, and also to solve many personal and social problems.